Costs of a Work-Family Intervention: Evidence from the Work, Family, and Health Network. Issue 4 (March 2014) - Barbosa, Carolina; Bray, Jeremy W.; Brockwood, Krista; Reeves, Daniel
Purpose: To estimate the cost to the workplace of implementing initiatives to reduce work-family conflict. Design: Prospective cost analysis conducted alongside a group-randomized multisite controlled experimental study, using a microcosting approach. Setting: An information technology firm. Subjects: Employees (n = 1004) and managers (n = 141) randomized to the intervention arm. Intervention: STAR (Start. Transform. Achieve. Results.) to enhance employees' control over their work time, increase supervisor support for employees to manage work and family responsibilities, and reorient the culture toward results. Measures: A taxonomy of activities related to customization, start-up, and implementation was developed. Resource use and unit costs were estimated for each activity, excluding research-related activities. Analysis: Economic costing approach (accounting and opportunity costs). Sensitivity analyses on intervention costs. Results: The total cost of STAR was $709, 654, of which $389, 717 was labor costs and $319, 937 nonlabor costs (including $313, 877 for intervention contract). The cost per employee participation in the intervention was $340 (95% confidence interval: $330–$351); $597 ($561–$634) for managers and $300 ($292–$308) for other employees (2011 prices). Conclusion: A detailed activity costing approach allows for more accurate cost estimates and identifies key drivers of cost. The key cost driver was employees' time spent on receiving the intervention. Ignoring this cost, which is usual in studies that cost workplace interventions, would seriously underestimate the cost of a workplace initiative.